Caso clínico: utilidad de la tomografía computada en la detección de cuerpos extraños del tracto aerodigestivo - Naser G., Alfredo; Nazar S., Rodolfo; Medel, Sebastián; Gormaz B., Juan Pablo (Revista Hospital Clínico Universidad de Chile, 2007)
We present the case of a 35 years old female patient with an impacted fish bone in the upper aerodigestive tract. In the initial assessment with physical examination, simple radiology study and fiberoptic endoscopy the fish bone couldn’t be found, so a Computed Tomographic (C.T.) study was performed showing a foreign body image in the right pyriform sinus. A direct laryngoscopy is performed removing successfully the fish bone. A bibliographic revision showed that C.T. has a sensibility of 100% and a specificity of 97% in the recognition of aerodigestive foreign body, while simple radiology has a sensibility of 15,9% and specificity of 99,5%, duemainly because of the variable degree of calcification of the patient’s laryngeal cartilages and the characteristics of the consumed fish (sweet or salad water origin, size of the fish, bone or cartilaginous fish, and depth of habitat).